Pivoting Culinary Arts Education During COVID-19 Part One - Adrian Woodhouse; Steve Ellwood (Journal of Innovation in Polytechnic Education)
As culinary educators, we have a long history of teaching our craft within a hands-on master apprentice learning environment . Since the dark ages, it has been typical for the trainee chef to physically stands by the side of their master and be guided in the development of their technical and cognitive skills. However, through the onset of Covid 19 in early 2020, the traditional ‘hands-on’ master-apprentice mode of learning was disrupted by lockdown and the inevitable of distance learning. In response to this, disruption The Food Design Institute at Otago Polytechnic, New Zealand quickly pivoted its mode of curriculum delivery from on-campus face to face learning to on-line distance learning.